Disentangling the firm growth process: evidence from a recursive panel VAR - Alexander Coad (Max Planck Institute of Economics, 2007)
We attempt to describe the coevolution of employment growth, sales growth and growth of profits in a panel of French manufacturing firms 1996-2004. Our analysis entails 'recursive' panel vector autoregressions, whereby we impose the structure of employment growth leading to contemporaneous sales growth, which in turn is associated with contemporaneous growth of profits. We observe that whilst employment growth has a direct negative association with profit growth, there are indirect effects through which employment growth leads to sales growth which in turn has a large effect on profits growth. The net effect of employment growth is thus positive growth of profits. Counter to some 'replicator dynamics' theories of industrial development, profit growth is not followed by much subsequent growth of employment.
Keywords: L20; L25; 330; Firm Growth; Panel VAR; Recursive VAR; Employment Growth; Industrial Dynamics; Unternehmenswachstum; Verarbeitendes Gewerbe; Personalbestand; Umsatz; Gewinn; Evolutionsökonomik; Industrieökonomik; Frankreich